A Governance Approach: Exploring the PMO Characteristics on Project Success and Failure - Alaray, Noora (2016)
Research on project management office (PMO) has revealed different perspectives as to how PMO should be implemented. Although it is recognized that PMO has been around as early as in the 1990s, recent study shows that many has just been created or restructured (Kerzner, 2003), but there value has constantly been a thing of discuss. In this study, the purpose is to explore the role of PMO and understand how PMO’s contributes to project success or failure, approach which is defined through governance. In order to explore the issue surrounding this fate, a triangulated approach was adopted so that facts can be capture from different perspectives such that the problem definitions underlying this research study can be addressed. The study was basically a descriptive one, and was design using a qualitative and quantitative methods in its approach to collect data. While the approach may read as being conducted sequentially, it was actually carried out using a concurrent approach, in order that a confirmatory to existing literatures can be ascertain on this issue. The study employed the use of questionnaire and interviews as a means to elicit information from participates. The questionnaires questions focused on the PMO characteristics as defined by functions, contributions, and structure, whereas, the interviews uses a structured interview format to gather the theoretical perspective of governance in relation to PMO on project success and failure. The outcomes as in the case of the qualitative study depicts some descriptive codes/categories/themes pertinent to the successful establishment and functioning of PMOs, and this includes: structure; leadership; management; well governed; flexibility; risk management among other. On the other hand, the quantitative study revealed the importance of those PMO variables via a weighted average, and subsequently, the percentage relationship were explained. It was noted that the research study does not reveal the sector of concern, but acted on the broader orientation of PMOs. As such, proffers for future studies to be carried out in this regard. However, the practical implications is that PMO is a Center of Excellency whose standards and objectives are applicable on a broader view. It was noted that the concerned organization i.e. ABC would benefit immensely from the study’s findings because it was actually design to understudy the problems confronting that organization. Hence, certain recommendations have been suggested as to how those problems can be addressed, and these includes: organizational business initiatives should pay attention to the leadership, standards, management etc. and juxtapose their needs with the necessary PMO characteristics by importance as identified in this study.